Sort term cryo-milt preservation of Pangasianodon hypophthalmus at the freshwater station of BFRI in Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A total of 50 sub-adults of Pangasianodon  hypophthalmus averaging 3.0 kg were stocked in a pond having an area of 0.2 ha.  During winter months, fishes were fed with commercially available pelleted feed containing about 28% protein at the rate of 1.5% body weight daily while feeding rate was 3% during summer months. For augmentation of gonadal maturation, water shower was provided in the pond during winter months. Females were found with bulging belly and male with running milt during spawning season. Milt sample was expelled from mature and healthy brood by gentle abdominal pressure and collected into a clean and dry tube of 5 ml capacity.  The milt samples were primarily placed in sealed ice box for 2-3 minutes then it was stored in a normal freezer for 20 minutes at 0 to 40C and then milt was stored in a deep freezer at -150C.  Dimethyl-sulphoxide (DMSO) was used as cryo-protectant and phosphate buffered saline was used as extender.  Cryo-tubes were leveled as A, B and C for storing 4, 8 and 12 hours, respectively.  Leveled cry-tubes ware placed in the refrigerator for 15 min to reduce temperature to 4°C before fast freezing in the freezer. Then the tubes were stored in a deep freezer at -15°C.  Sperm motility of fresh milt was recorded as 95%. In the thawing process, these cryo tubes were first transferred into refrigerator for 20 min to allow the milt to thaw from -20°C to 4°C inside the refrigerator.  Thereafter, cryo tubes were transferred at room temperature and allowed to stand 5 min before mixing with female eggs. Thawed milt was added to the fresh eggs of Pangasius hypophthalmus and thoroughly mixed. After approximately 3 minutes, water was added to water-harden the eggs.  Motility of cryo-preserved milt was nil.  It is probably due to improper method applied to preserve the milt.  For short-term preservation, milt was stored in ice box for 2, 4 and 8 hours.  Motility rate of Pangasius hypophthalmus ranged between 5 and 50% and fertilisation rate varied between 1 and 40%, respectively. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 398-401